2014
DOI: 10.1371/journal.pone.0114740
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of Nanosilver-Functionalized PMMA Bone Cement on Primary Human Mesenchymal Stem Cells and Osteoblasts

Abstract: Peri-prosthetic infections caused by multidrug resistant bacteria have become a serious problem in surgery and orthopedics. The aim is to introduce biomaterials that avoid implant-related infections caused by multiresistant bacteria. The efficacy of silver nanoparticles (AgNP) against a broad spectrum of bacteria and against multiresistant pathogens has been repeatedly described. In the present study polymethylmethacrylate (PMMA) bone cement functionalized with AgNP and/or gentamicin were tested regarding thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 52 publications
5
18
1
Order By: Relevance
“…In the present study, determination of osteogenic cell differentiation revealed a significantly reduced ALP enzyme activity after 24 and 72 h on all cement surfaces compared to TCP, whereas the results were higher after incubation for 72 h. The latter findings are in line with the previously published results of Pauksch et al [22]. In contrast to our study, however, the authors observed no significant change in ALP enzyme activity for osteogenic cells cultivated on PMMA surfaces.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, determination of osteogenic cell differentiation revealed a significantly reduced ALP enzyme activity after 24 and 72 h on all cement surfaces compared to TCP, whereas the results were higher after incubation for 72 h. The latter findings are in line with the previously published results of Pauksch et al [22]. In contrast to our study, however, the authors observed no significant change in ALP enzyme activity for osteogenic cells cultivated on PMMA surfaces.…”
Section: Discussionsupporting
confidence: 90%
“…Confirming their results, we also identified a significant reduction in cell viability and DNA content on Palacos R and Palacos R+G surfaces after 24 h. After 72 h, a considerably higher cell viability and DNA content was observed for all surfaces. Interestingly, the increase was higher for the cement groups than for the control on TCP, confirming the results of Pauksch et al [22]. The authors hypothesized that the increasing confluence of the cells on TCP led to a decreased viability, as high cell numbers often cause a stop in proliferation and a decline in viability.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The great merit of the AgNP immobilization is that it presumably nullifies its negative influence on eukaryotic cells; however, only few AgNP-support systems has been analyzed. The investigation of nanosilver-functionalized polymethylmethacrylate bone cement has demonstrated suitable cytocompatibility with primary human mesenchymal stem cells and osteoblasts [22]. Foregoing properties were confirmed in further research.…”
Section: Introductionmentioning
confidence: 73%
“…4 AgNPs are known to induce differentiation based on their concentration in a time-dependent manner in various types of stem cells including human adipose-derived stem cells, hMSCs, and osteoblasts. 64,65 Previous studies have shown that internalized silica nanoparticles have no apparent deleterious effects on the morphology, proliferation, viability, and differentiation efficiency of mesenchymal stem cells. 66,67 The findings from our study suggest that biologically prepared AgNPs seem to be less toxic than AgNO 3 at tested concentrations in F9 cells.…”
Section: Agnps Induce the Expression Of Differentiation Markers And Ementioning
confidence: 99%